Pengembangan Instrumen Kebijakan Pencegahan Bullying Sebagai Upaya Menciptakan Sekolah Ramah Anak di Kota Surabaya - Nurul Aulia Ridwan; Agus Sukristyanto; Muhammad Roisul Basyar (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This study discusses the development of bullying prevention policy instruments as an effort to create Child-Friendly Schools in Surabaya City. This study uses a descriptive qualitative method with data collection through observation, interviews, and documentation. Informants in the study from the head of the Middle School student work team of the Surabaya City Education Office, the Head of the Women and Children Protection Division of the Women's Empowerment and Child Protection Office and Population Control and Family Planning of Surabaya City, the violence prevention and response team at SMPN 61 Surabaya, the violence prevention and response team at SMP Islam Shafta Surabaya, the violence prevention and response team at SMP Wijaya Putra Surabaya. Analysis of the development of bullying prevention policy instruments as an effort to create Child-Friendly Schools in Surabaya City uses the Howlett and Ramesh theory with 3 instruments, namely: (1) mandatory instruments (2) voluntary instruments and (3) mixed instruments. According to the Regulation of the Minister of State for Women's Empowerment and Child Protection of the Republic of Indonesia Number 8 of 2014 concerning Child-Friendly School Policies at SMPN 61 Surabaya, SMP Islam Shafta, and SMP Wijaya Putra, 6 indicators have been implemented in creating Child-Friendly Schools. But there is still something lacking. And of the 3 schools, the most complete in implementing Child-Friendly Schools is SMPN 61 Surabaya. So other schools also need to follow the example of SMPN 61 Surabaya.